2022
DOI: 10.3389/fimmu.2022.915590
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Long-Term Survival and Safety of Haploidentical Hematopoietic Stem Cell Transplantation After CAR-T Cell Therapy or Chemotherapy in Pediatric Patients With First Relapse of B-Cell Acute Lymphoblastic Leukemia Based on MRD-Guided Treatment

Abstract: Measurable residual disease (MRD) positivity before haploidentical hematopoietic stem cell transplantation (haplo-HSCT) is an independent prognostic factor in determining outcomes in patients with B-cell acute lymphoblastic leukemia (ALL). In this study, we conducted a parallel comparison of the efficacy and safety in patients with suboptimal MRD response after reinduction who underwent haplo-HSCT after chimeric antigen receptor T-cell (CAR-T) therapy or chemotherapy. Forty B-cell ALL patients who relapsed aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…A total of 10/13 (76.9%) patients developed grade 1 to 2 aGVHD, and 9/13 (69.2%) experienced cGVHD, including 3 of them (23.1%) suffering from mid-to-severe cGVHD. The incidence of aGVHD and cGVHD observed in the present study was consistent with that observed in our previous studies 12,13 . In conclusion, our study showed that anti-CD19 CAR-T therapy followed by allo-HSCT was safe for Ph-positive B-ALL pediatric patients and can improve the survival of some patients, but it is worse than that of Ph-negative patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A total of 10/13 (76.9%) patients developed grade 1 to 2 aGVHD, and 9/13 (69.2%) experienced cGVHD, including 3 of them (23.1%) suffering from mid-to-severe cGVHD. The incidence of aGVHD and cGVHD observed in the present study was consistent with that observed in our previous studies 12,13 . In conclusion, our study showed that anti-CD19 CAR-T therapy followed by allo-HSCT was safe for Ph-positive B-ALL pediatric patients and can improve the survival of some patients, but it is worse than that of Ph-negative patients.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of aGVHD and cGVHD observed in the present study was consistent with that observed in our previous studies. 12,13 In conclusion, our study showed that anti-CD19 CAR-T therapy followed by allo-HSCT was safe for Ph-positive B-ALL pediatric patients and can improve the survival of some patients, but it is worse than that of Ph-negative patients. Nevertheless, this study had certain limitations.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Lymphoid malignant hematological disease patients had a lower CIR rate than myeloid malignant hematological diseases although in multivariate analysis there were no differences in OS, LFS, and CIR. We believe that these outcomes may be related to the limited number of cases in this study, as we can assume that patients who have received CAR-T have a better chance of achieving CR/MRD negativity than those who received traditional chemotherapy, and this is consistent with prior studies ( 38 , 39 ). As more immunotherapies have become available, we anticipate that there will be more candidates for a second HSCT with improved performance and remission status, ultimately leading to better outcomes for patients who receive a second HSCT.…”
Section: Discussionsupporting
confidence: 87%
“…Response to CAR-T cell therapy in pediatric and young adult patients with refractory and relapsed B-ALL is generally favorable and durable, with 63% overall survival rate at 36 months, and an estimated 9.28 quality-adjusted life-years (QALYs) gained (10,11). Survival in relapsed pediatric B-ALL patients with measurable residual disease (MRD) positivity following re-induction who are treated with CAR-T cell therapy prior to HSCT has been shown to improve survival compared to patients treated with chemotherapy prior to HSCT (12). Patients who undergo CAR-T cell therapy are at increased risk of infection due to multiple factors including prior chemotherapy and cancer treatment, lymphodepleting chemotherapy during the CAR-T cell process, cytokine release syndrome in the immediate post CAR-T cell infusion time period, and hypogammaglobulinemia (13).…”
Section: Discussionmentioning
confidence: 99%